Training for improved neuro-muscular control of balance in middle aged females. Issue 1 (January 2016) - Anderson, Gregory S.; Deluigi, Fabio; Belli, Guido; Tentoni, Claudio; Gaetz, Michael B.
Summary: This study examined improvements in static balance and muscle electromyographic (EMG) activity following a four week progressive training program in 16 middle aged females (mean age = 46.9 ± 8.7 yrs; height 161.1 ± 6.0 cm; weight 65.4 ± 11.2 kg). Participants trained 3 times per week for 4 weeks, for 50 min per session, progressing base of support, stability, vision, resistance and torque in each of six basic exercises. Pre and post training measures of balance included feet together standing, a tandem stance and a one-leg stand (unsupported leg in the saggital plane) performed with the eyes closed, and a Stork Stand (unsupported leg in the frontal plane) with both eyes open and closed. In each position postural deviations were tallied for each individual while muscle recruitment was determined using root mean squared (RMS) EMG activity for the soleus, biceps femoris, erector spinae, rectus abdominis and internal oblique muscles of the dominant foot side. Balance scores were significantly improved post training in both the Balance Error Score System ( p  < 0.05) and stork stand positions ( p  < 0.01). Muscle activity was reduced post-training in all muscles in each condition except the soleus in the tandem position, although not all significantly. Reduced biceps femoris activity suggest that improved core stability allowed participants to move from a hip to an ankle postural control strategy through improved coordination of muscles involved in balance and reduced body sway. The core muscles were able to control body position with less activity post training suggesting improved muscle coordination and efficiency. These results suggest that short term progressive floor to BOSU™ balance training can improve standing balance in middle aged women.